QUALITY OF LOW COST HOUSING SETTLEMENT PROJECT - Acwin Dwijendra, Ngakan Ketut (Jurnal Natah; Vol. 2, No. 2 Agustus 2004)
Housing refers to both the physical product and the process of its attainment. Housing is perceived according to its performance and its usefulness varies with the level of comfort and hygiene it provides. The importance of people in housing is recognised not when housing complies with municipality by laws, but when people come to live in it and it has to be acceptable in a community. Housing also means privacy and is an expression of ways of life, aspirations and social relationships. Therefore, housing is the provision of comfortable shelter with available infrastructure, services and facilities that address the people needs. Denpasar have large the low-income housing and settlement provided by PERUMNAS and private developers as well. Yet, the fast growing of low-income housing projects in Denpasar is not guaranteed addressing the living conditions of low-income group. In fact, most housing projects, which is built both by private developers and PERUMNAS, lack physical quality, lack infrastructure and lack public facilities. This paper will try to investigate the role of households as consumers and the role of developers in providing better quality low-cost housing projects in Denpasar. The result is that the low quality of low cost housing project, caused by lack of instruments to force the builders to provide better quality and the households themselves also have no means to influence the quality of project as well.
Keywords: quality, low cost housing project, low income group.